2020
DOI: 10.1002/cbdv.202000199
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Ginseng and the Seed of Zizyphus jujuba var. spinosa on Gut Microbiota of Rats with Spleen Deficiency

Abstract: Ginseng and the seed of Zizyphus jujuba var. spinosa, which are traditional Chinese medicinal materials, were often used in ancient Chinese recipes as a pair of medicines. They can replenish the primordial qi and tonify the spleen. This study investigated the effects of ginseng and the seed of Zizyphus jujuba var. spinosa (GS) extract on gut microbiota diversity in rats with spleen deficiency syndrome (SDS). A total of 52 compounds (including 16 flavonoids, 35 saponins, and 1 alkaloid) were identified and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…found that the extract of ginseng and the seed of Zizyphus jujuba var. spinosa significantly increased the relative abundance of Firmicutes in rats with spleen deficiency syndrome [20] . These results were consistent with the results of the current study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…found that the extract of ginseng and the seed of Zizyphus jujuba var. spinosa significantly increased the relative abundance of Firmicutes in rats with spleen deficiency syndrome [20] . These results were consistent with the results of the current study.…”
Section: Resultssupporting
confidence: 93%
“…spinosa significantly increased the relative abundance of Firmicutes in rats with spleen deficiency syndrome. [20] These results were consistent with the results of the current study. A number of scholars focusing on the therapeutic effects of ginseng polysaccharides on diarrhoea mice have found that relative to the blank control group, the antibiotic-induced diarrhoea mouse model had a significantly increased abundance of Bacteroidetes.…”
Section: Key Phylotypes Of the Gut Microbiotasupporting
confidence: 93%
“…Escherichia-Shigella has been known as harmful bacteria because of its poor ability to produce SCFA and could cause intestinal inflammation [ 58 ]. The negative correlation between β -glucosidase and Escherichia-Shigella has never been reported, but the proliferation of Escherichia-Shigella could be inhibited by traditional Chinese medicinal materials, which would then influenced glucose and amino acid metabolism [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus genus includes common probiotic species that can repair damaged intestinal mucosa ( Wu et al, 2020 ), improve aerobic endurance capacity and energy harvest ( Huang et al, 2018 ), and resist the invasion of Shigella flexneri in human intestinal epithelial cells ( Song et al, 2020 ). Some studies have demonstrated that in the gut microbiota of SDS rats Lactobacillus decline and Proteobacteria increase ( Ma et al, 2019 ; Gao et al, 2020 ; Li et al, 2020 ; You et al, 2020 ). Similarly, we observed that in SDS mice Shigella abundance increased, whereas CPP intervention markedly enriched Lactobacillus and inhibited Shigella .…”
Section: Discussionmentioning
confidence: 99%